Implementasi kurikulum merdeka belajar pada pembelajaran PJOK - Irvansyah, Dicky; Wahyudi, Arief Nur; Darumoyo, Kuncoro (Universitas Hamzanwadi, 2023)
This study aims to determine the implementation of the independent learning curriculum in PJOK learning. The problem is that the Ministry of Education and Culture issued a regulation in the form of an independent learning curriculum. Methods using descriptive qualitative. Sources of data using primary data consist of school principals, PJOK teachers and students. Data collection techniques using observation, interviews, documentation. Data analysis techniques use data condensation, data presentation, drawing conclusions. The data collection instrument uses a data validity test, a credibility test. The results of this study indicate that the implementation of the independent learning curriculum in PJOK learning is carried out optimally. Even though there are obstacles to the teacher's knowledge regarding the understanding of independent learning curriculum learning. In addition, there is a shortage of teachers in preparing the independent learning curriculum. The key to success in implementing the independent learning curriculum in PJOK learning is that there must be a willingness to make changes in accordance with the provisions set by the government and see the potential that exists. In conclusion, planning in independent learning is not fully in accordance with the theory, it does not show CP, ATP and MA in the learning process.